Processing of Customized Automotive and Oil and Gas Components – Nickel Aluminium Bronze and Aluminium Silicon Material by Using Metal Casting Techniques - Mohd Rashidi, Maarof (Faculty of Mechanical & Automotive Engineering Technology, 2022)
The academic year of 20112022 which begins in October 2021 where students continue to undertake their face-to-face lecture or laboratory sessions as restrictions imposed by the MCO are gradually being eased up.